PENINGKATAN PENGETAHUAN ANGGOTA KELOMPOK WANITA TANI GUYUP RUKUN KALIMUNDU DALAM PEMBUATAN DAN PEMASARAN TEH CELUP BUNGA TELANG - Wahyuningsih, Iis; Sri Rejeki, Marsudi Endang; Kintoko, Kintoko; Khusnul, Latifah (Jurnal Bakti untuk Negeri, 2025)
This community service activity aimed to improve the knowledge and skills of the members of  KWT Guyub Rukun in Kalimundu in the production and marketing of butterfly pea flower tea bags. A total of 20 participants took part in a series of four  sessions: post-harvest handling, tea bag production, packaging, and marketing including the determination of the cost of goods sold. Pretest and posttest evaluations indicated an increase in participants’ understanding across all sessions. In the post-harvest training, participants showed better comprehension of proper harvesting time and drying methods that help maintain material quality. In the tea-making session, all indicators showed score improvement, with pretest scores ranging from 33.33% to 91.67%, and increasing to 100% on most posttest questions. During the packaging session, participants began to understand the importance of using packaging that meets standards and has attractive visual appeal. Meanwhile, the marketing and COGS session showed significant improvement, especially in identifying effective promotional media and understanding cost components, with some indicators increasing from 12 to 16 correct responses. These results reflect the effectiveness of the training in enhancing the technical and entrepreneurial capacities of KWT members, and mark a strategic step in empowering women through locally based economic development.